Evaluation and Optimization of DNA Extraction Protocol from Leaves of an Endangered Forest Tree Species Strychnos potatorum Linn. F - Kagithoju, Srikanth; Godishala, Vikram; Banala, Mahitha; Nanna, Rama Swamy (Indian Forester, 2018)
Although, several protocols are available for isolation of DNA form plants, it is essential to compare and establish a suitable protocol for isolation of intact and high quality genomic DNA in medicinal plants. This is fundamental in plants containing active biomolecules and is also essential and important in downstream studies like PCR, genetic transformation and genetic evolution studies etc. In the present investigation, three different cetyl trimethyl ammonium bromide (CTAB) based protocols have been used, compared and finally an efficient modified CTAB protocol was developed for DNA isolation from fresh leaves of medicinally important forest tree species Strychnos potatorum Linn. F. Key steps modified in the CTAB protocol were avoiding of Ã¢-mercapto ethanol and addition of polyvinyl pyrrolidine (PVP) and Ascorbic acids. This protocol yielded genomic DNA with excellent spectral qualities, increased yield (1.06Î¼g/g) and purity (1.836). DNA extracted by this method is subjected for PCR amplification using an arbitrary RAPD primer OPA 10 and resulted in better amplification. Thus, the present modified Saghai-Maroof’s CTAB protocol developed for isolation of genomic DNA is an efficient, inexpensive, simple, rapid, high yield, pure and suitable for further molecular studies in S. potatorum a medicinally important forest tree.